Removal of Methylene Blue from Aqueous Solutions by Using Nance (Byrsonima crassifolia) Seeds and Peels as Natural Biosorbents - Lorena Robles-Melchor; Maribel Cornejo-Mazón; Diana Maylet Hernández-Martínez; Gustavo F. Gutiérrez-López; Santiago García-Pinilla; Edgar Oliver López-Villegas; Darío Iker Téllez-Medina (Journal of Chemistry)
Contamination of effluents with chemicals is a serious problem that impacts human health. Methylene blue is a cationic dye found frequently in industrial and urban sewages. In this work, dried grinded seeds and peels of nance were used as biosorbents in aqueous solutions at pH 7 and 10 (simulating urban and textile effluents) finding that Langmuir and Freundlich isotherms adequately described the sorption. Adsorption efficiencies were larger than 98% in all cases and slightly lower at pH 7 due to the closeness with the point of zero charge (pzc) of seeds and peels of nance (5.96 and 3.42, respectively). In all cases, Langmuir adsorption was favorable (RLa < 1), and Gibbs free energy of adsorption was negative indicating spontaneity, and since these values were larger than −80 but lower than 0 kJ/mol, the MB removal process was mainly due to physical interactions, a characteristic of physical adsorption. No significant differences were found amongst bulk mass transfer coefficients for the adsorption of both sorbents, indicating that both bioadsorbents had the same hydrodynamic and driving forces as well as depicted similar MB-adsorbent affinities. Interaction of MB with adsorbents was corroborated by FTIR spectroscopy, and the sorption was evidenced by scanning electron microscopy and image analysis which indicated that both adsorbents had fractal structures.